Comprehensive Mass Spectral Libraries of Human Thyroid Tissues and Cells - Lu Li; Wenhao Jiang; Wenjun Wei; Gnana P. Krishnamoorthy; Pingping Hu; Mengni Chen; Vera Tiedje; Adrián Acuña-Ruiz; He Wang; Zhihong Wang; Jianbiao Wang; Hanqing Liu; et al. (Scientific Data)
Abstract Thyroid nodules are a common endocrine condition with an increasing incidence over the decades. Data-independent acquisition has been widely utilized in discovery proteomics to identify disease biomarkers and therapeutic targets. To analyze the thyroid disease-related proteome in a high-throughput, reproducible and reliable manner, we introduce thyroid-specific peptide spectral libraries. Here, we generated four deep-coverage libraries through four mass spectrometers comprising Q Exactive HF, Orbitrap Exploris 480, ZenoTOF 7600, and timsTOF Pro. These libraries encompass over 215,000 precursors, 172,000 peptides, and 12,000 proteins, derived from 245 tissue samples across nine histological types and 50 cell lines across six histological types. Moreover, the spectral libraries are applied to nine types of thyroid samples to facilitate the exploration of disease-specific proteins. Our spectral libraries serve as a valuable resource for analyzing thyroid protein content, facilitating deeper insights into thyroid disorders.